Differential Flag Leaf and Ear Photosynthetic Performance Under Elevated (CO2) Conditions During Grain Filling Period in Durum Wheat - Gámez, Angie L.; Vicente, Rubén; Sanchez-Bragado, Rut; Jauregui, Iván; Morcuende, Rosa; Goicoechea, Nieves; Aranjuelo, Iker (Frontiers in Plant Science, 2020)
Elevated concentrations of CO2 [CO2] in plants with C3 photosynthesis metabolism, such as wheat, stimulate photosynthetic rates. However, photosynthesis tends to decrease as a function of exposure to high [CO2] due to down-regulation of the photosynthetic machinery, and this phenomenon is defined as photosynthetic acclimation. Considerable efforts are currently done to underline the effect of photosynthetic tissues, such us spike, in grain filling. There is good evidence that the contribution of ears to grain filling may be important not only under good agronomic conditions but also under high [CO2]. The main objective of this study was to compare photoassimilate production and energy metabolism between flag leaves and ears (glumes) of wheat (Triticum turgidum L. subsp. durum cv. Amilcar) plants exposed to ambient (a[CO2]) and elevated (e[CO2]) [CO2] (400 and 700 µmol mol-1, respectively). Elevated CO2 had a differential effect on the responses of flag leaves and ears. The ears showed higher gross photosynthesis and respiration rates compared to the flag leaves. The higher grain dry mass (DM) contributed to increase ear carbohydrate and respiration rates. Our results support the concept that acclimation of photosynthesis to e[CO2] is driven by sugar accumulation, reduction in N concentrations and repression of genes related to photosynthesis, glycolysis and the tricarboxylic acid cycle, and that these were more marked in glumes than leaves. These findings provide information about the impact of e[CO2] on ear development during the grain filling stage and are significant for understanding the effects of increasing [CO2] on crop yield.